Different Forms of Time in Gulzar's Poems - Qarni, Muhammad Awais; Bashir, Sonia; Muhammad, Wali (sourcecoder, 2023)
Time is not a new topic in Urdu poetry. In different eras, poets have been trying to understand and explain it according to their own understanding. With some poets, it has been a permanent subject, while in the poetry of other many poets it has been treated as a secondary subject. Time is also a constant theme in Gulzar's poems. He did not try to create philosophies, but he tried to present the time according to his personal feelings. Although his study and empathic style are profound but his inner artistic talent is capable to present the complex issues of time in a personal and creative way. In this research paper, a scholarly analysis of different forms of time in Gulzar's poems has been presented in full detail.